Detection of porcine epidemic diarrhea virus–neutralizing antibody using high-throughput imaging cytometry. (March 2020) - Sarmento, Luciana V.; Poonsuk, Korakrit; Tian, Liying; Mora-Díaz, Juan C.; Main, Rodger G.; Baum, David H.; Zimmerman, Jeffrey J.; Giménez-Lirola, Luis G.
Porcine epidemic diarrhea virus (PEDV) is an emerging porcine coronavirus that causes a tremendous economic burden on the swine industry. The assessment of PEDV-neutralizing antibody levels provides a valuable tool to assess and predict herd immunity. We evaluated the performance of a PEDV imaging cytometry–based high-throughput neutralization test (HTNT) and compared the HTNT to a fluorescent focus neutralization (FFN) assay using serum samples from pigs of known PEDV infection status ( n = 159). Estimates of diagnostic sensitivity and specificity for HTNT and FFN assays derived from receiver-operator characteristic (ROC) curve analyses showed that both PEDV FFN and HTNT provided excellent diagnostic performance. However, in the laboratory, imaging cytometry provided an objective and semi-automated approach that removed human subjectivity from the testing process and reduced the read-time of a 96-well plate to < 4 min. In addition, imaging cytometry facilitated the rapid collection and long-term storage of test images and data for further evaluation or client consultation. For PEDV and other pathogens, imaging cytometry could provide distinct advantages over classic virus neutralization or FFN assays for the detection and quantitation of neutralizing antibody.